Concept of health in the view of diabetic patients: A qualitative study - valiee, sina; Moridi, golrokh; Fathi, Mohammad; Nikbakht Nasrabadi, Alireza; Rezaei Farimani, Mostafa (Advances in Nursing & Midwifery, 2012)
Concept of health in the view of diabetic patients: A qualitative study Valiee, S. 1 * (MSN); Moridi, G. 2 (MSN); Fathi, M. 3 (MSN); Nikbakht Nasrabadi, A. R. 4 (PhD); Rezaei Farimani, M.5 (BSN) 1. Lecturer, Dept. Medical Surgical, Faculty of Nursing and Midwifery, Kurdistan University of Medical Sciences, Kurdistan, Iran. PhD candidate, Faculty of Nursing and Midwifery, Tehran University of Medical Sciences, Tehran, Iran 2. Lecturer, Dept. Pediatric, Faculty of Nursing and Midwifery, Kurdistan University of Medical Sciences, Kurdistan, Iran. 3. Lecturer, Dept. Medical Surgical, Faculty of Nursing and Midwifery, Kurdistan University of Medical Sciences, Kurdistan, Iran 4. Associated Professor, Dept. Medical Surgical, Faculty of Nursing and Midwifery, Tehran University of Medical Sciences, Tehran, Iran 5. Lecturer, Dept. Medical Surgical, Faculty of Nursing and Midwifery, Tehran University of Medical Sciences, Tehran, Iran. Abstract Background and aim Feeling of health is subjective and unique and health criterion varies in different age, cultural and socioeconomic groups. Illness can have a great effect on individual’s feeling and definition of health and well being. The aim of this study was to explore the meaning of health concept in the view of diabetic patients. Materials and methods This study was qualitative, semi structured interviews were conducted with 20 diabetic patients who attended to the diabetes clinic of Sanandaj Tohid Hospital. Interviews were transcribed and analyzed using conventional content analysis, and codes and themes were derived from participant’s responses. Findings Based on the findings of study five major themes about health emerged: intact body and happiness, life without any limits, peace of mind, spirituality and absence of complications. Conclusion Health definition based on specific conditions of any culture and group that affect health behavioral. Based on emerged themes, health care providers must consider these themes and seek ways to achieve health in diabetic patients and use them in care plans. Keywords: Health, Diabetes, Qualitative study, Conventional content analysis, Nursing. *Corresponding Author: Sina Valiee, Faculty of Nursing and Midwifery, Kurdistan University of Medical Sciences, Pasdaran St, Kurdistan, Iran. E-mail: valiee@muk.ac.ir